2022
DOI: 10.1080/02134748.2022.2038421
|View full text |Cite
|
Sign up to set email alerts
|

The roles of national and global identities and leaders in the acceptance of COVID-19 vaccines developed by different countries (Los roles de las identidades y los líderes nacionales y globales en la aceptación de las vacunas contra la COVID-19 desarrolladas por diferentes países)

Abstract: The roles of national and global identities and leaders in the acceptance of COVID-19 vaccines developed by different countries (Los roles de las identidades y los líderes nacionales y globales en la aceptación de las vacunas contra la COVID-19 desarrolladas por diferentes países)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
(156 reference statements)
0
1
0
1
Order By: Relevance
“…The success in controlling the pandemic within a country, and in turn across the world, appears to depend on a variety of social identity-related factors ( Akfırat et al, 2022 ; Van Bavel et al, 2022 ). For example, Akfirat et al showed that national identification positively predicted acceptance of national vaccines and negatively predicted acceptance of Western vaccines; people's evaluations of their leaders also mediated both relationships.…”
Section: The Current Studymentioning
confidence: 99%
“…The success in controlling the pandemic within a country, and in turn across the world, appears to depend on a variety of social identity-related factors ( Akfırat et al, 2022 ; Van Bavel et al, 2022 ). For example, Akfirat et al showed that national identification positively predicted acceptance of national vaccines and negatively predicted acceptance of Western vaccines; people's evaluations of their leaders also mediated both relationships.…”
Section: The Current Studymentioning
confidence: 99%
“…Dalam penanganan pandemi covid-19, berbagai studi telah dilakukan dengan menekankan pada tiga pendekatan awal dengan lensa psikologi kepemimpinan (Akfirat et al, 2022;Balasubramanian & Fernandes, 2022;Duong et al, 2020;Kapucu & Moynihan, 2021;Nguyen, 2022;Wilson, 2020;Yeo & Jeon, 2021). Kontras dengan beberapa studi tersebut, penelitian ini berkeyakinan bahwa kepemimpinan dalam penanganan pandemi tidak semata-mata bergantung pada gaya, situasi maupun sifat personal yang dimiliki seorang pemimpin.…”
Section: Pendahuluanunclassified